DO THE NEWS AFFECT THE EUR/ALL EXCHANGE RATE VOLATILITY? - Gentjan ÇERA; Eda DOKLE; Edmond ÇERA (Economic Review)
Since the early 1990s, Albania has adopted the flexible exchange rate regime. A vast empirical literature on exchange rate is focused on modeling its volatility. In contrast, this paper provides empirical analysis regarding the news impact on the EUR/ALL exchange rate volatility, using TGARCH model. We argue that the series has three important features of asset return proposed by the theory: unpredictability, fat tails and volatility clustering. The results show the existence and importance of news impact on exchange rate return.